Active Fraction of Polyrhachis Vicina Roger (AFPR) Ameliorate Depression Induced Inflammation Response by FTO/miR-221-3p/SOCS1 Axis - He J; Xie J; Zhou G; Jia C; Han D; Li D; Wei J; Li Y; Huang R; Li C; Wang B; Wei C; et al. (Dove Medical Press, 2023)
Junhui He,1,* Jiaxiu Xie,1,* Guili Zhou,2,* Chunlian Jia,2 Dongbo Han,2 Dongmei Li,1 Jie Wei,1 Yi Li,1 Renshan Huang,1 Chunlian Li,1 Bo Wang,3 Chao Wei,3 Qibiao Su,4 Kedao Lai,1 Guining Wei1 1Department of Pharmacology, Key Laboratory of Quality Standards, Guangxi Institute of Chinese Medicine & Pharmaceutical Science, Nanning, 530022, People's Republic of China; 2Department of Pharmacology, Guangxi Medical University, Nanning, Guangxi, 530021, People's Republic of China; 3Guangxi Shuangyi Pharmaceutical Co., Ltd, Nanning, Guangxi, 530021, People's Republic of China; 4College of Health Science, Guangdong Pharmaceutical University, Guangzhou, 510006, People's Republic of China*These authors contributed equally to this workCorrespondence: Guining Wei, Department of Pharmacology, Guangxi Institute of Chinese Medicine & Pharmaceutical Science, Nanning, 530022, People's Republic of China, Email weiguining2013@163.com Qibiao Su, College of Health Science, Guangdong Pharmaceutical University, Guangzhou, 510006, People's Republic of China, Tel +8618376664440, Email suqibiao@163.comPurpose: Neuroinflammation is a significant etiological factor in the development of depression. Traditional Chinese medicine (TCM) has demonstrated notable efficacy in the treatment of inflammation. Our previous study surfaces that the active fraction of Polyrhachis vicina Roger (AFPR) has antidepressant and anti-neuroinflammatory effects, but the specific mechanisms remain to be elucidated. The objective of this study was to examine the impact of AFPR on inflammation in depression via the FTO/miR-221-3p/SOCS1 axis.Methods: Chronic unpredictable stress (CUMS)-induced rats and LPS-induced BV2 cells were employed to simulate depression models in vivo and in vitro. The levels of inflammatory factors were detected using the ELISA assay. The expression of genes and proteins was detected using qRT-PCR and Western blot. Gene interactions were detected using the dual luciferase reporter gene. Protein-RNA interactions were investigated using RNA methylation immunoprecipitation (MeRIP) and RNA immunoprecipitation (RIP). Neuroinflammation in the brain was examined through H&E staining, while neuronal apoptosis was assessed using TUNEL staining.Results: The results showed that AFPR ameliorated depression induced inflammation by increasing SOCS1 expression. However, SOCS1 was identified as a target of miR-221-3p. Overexpression of miR-221-3p decreased the expression of SOCS1 and increased the levels of NF-κB, IL-7, and IL-6. In addition, we found that miR-221-3p was regulated by FTO-mediated m6A modification through MeRIP and RIP experiments. Interference with miR-221-3p and overexpression of FTO resulted in increased SOCS1 gene expression and decreased levels of NF-κB, IL-7, and IL-6, which were reversed by AFPR.Conclusion: AFPR inhibits the maturation of pri-miR-221-3p through FTO-mediated m6A modification, reduces the production of miR-221-3p, increases the expression of SOCS1, and reduces the level of inflammation, thereby improving depressive symptoms. Keywords: depression, FTO, SOCS1, inflammation, Polyrhachis vicina Roger